National governance quality, COVID-19, and stock index returns: Oecd evidence - Hamza Almustafa (Economies, 2022)
This research argues that national governance quality may moderate the relationship between COVID-19 and stock returns across markets. Building on the well-established relationship between COVID-19 shock and stock returns, we focus on how the quality of a country's governance system affects the relationship between the COVID-19 crisis and stock returns. Using data from the World Governance Indicators, the World Bank, and the John Hopkins University Coronavirus Resource Centre (JHU-CRC) for 29 OECD markets from 23 January to 31 December 2020, our findings confirm this hypothesis. Our results suggest that, the estimated coefficient on the interaction term is negative (-0.004) and statistically different from zero at the 5% level of significance. This result can be inferred that the higher the national governance quality is, the weaker the effect of COVID-19 on stock returns will be. Specifically, the negative impact of COVID-19 on stock market returns was more pronounced in countries where the national governance quality index is lower. Our results also show a strong negative association between COVID-19 and stock market returns across the sample. The results are robust to changes in governance quality measures, estimation methods, and explanatory variables. The results have several policy implications such that better institutions may partially offset the adverse impact of the COVID-19 shock on stock market returns.
Keywords: E02; F65; G18; G34; G38; 330; COVID-19; national governance quality; OECD markets; stock index returns